Fatigue performance analysis for parts made by selective laser melting - Chee, Edmund Tong Jie (2017)
The recent popularity of additive manufacturing technology, specifically Selective Laser Melting (SLM), has promised to revolutionize the manufacturing industry by enabling manufacturers to fabricate components on site and on demand with minimum material wastage as compared to conventional manufacturing processes. Stainless steel 316L has a wide range of application ranging from medical equipment to the marine industry as it has excellent mechanical and corrosion resistant properties. Thus to enable the application of SLM to these industries, the production process and its mechanical behaviour has to be examined to ensure that it is suitable for its intended use. Therefore, the aim of this report is to evaluate the fatigue properties of Stainless Steel 316L manufactured by Selective Laser Melting (SLM). In this report, one of the variable parameters during the production process, laser power, and its effect on pores or voids within the component will be studied. The microstructural defects is then characterised by examining them through Light Optical Microscopy (LOM) and X-ray Computer Tomography (CT) then subjecting the samples to constant amplitude uniaxial fatigue loading to understand the effect of microstructural defects on the mechanical properties of the components. Finally, fractographic analysis is conducted on the fracture surface to investigate the mode of failure. Results from this study conclude that fatigue properties of SLM fabricated parts fared poorly in comparison to conventionally manufactured stainless steels. Fatigue test results show that laser power that lies between the ranges of +30% to -30% of the recommended power setting, Po, yielded the best fatigue performance. For samples that achieve 99% densification, the analysis of the average porosity findings from LOM and X-ray CT could not be clearly correlated to the fatigue performance, however, extreme value analysis of largest pore proves to be a more effective indicator of fatigue performance. Finally, fractographic analysis shows that internal defects like extensive cracking and porosity exhibited by the overheating and under heating of the sample respectively, contributed to the fatigue failure of the parts.